Ekstraksi Daun Kejibeling (Strobilanthes crispus) dengan Metode Continuous Ultrasound-Assisted Enzymatic Extraction: Pengaruh Temperatur dan Konsentrasi Enzim - Tania Surya Utami; Yuswan Muharam; Rita Arbianti; Naufal Azrizal Prasetyo; Randi Sitorus (Jurnal Teknik Kimia USU, 2024)
Continuous ultrasound-assisted enzymatic extraction (CUAEE) method has become a promising technique for extracting bioactive compounds from plant materials. In this study, the extraction of kejibeling (Strobilanthes crispus) leaves was carried out using the CUAEE method to optimize the extract yield. The experimental design involved extraction parameters including leaf particle size (d ≤0,177 mm), ethanol concentration (50%), extraction time (180 minutes), and varying parameters such as temperature (30 °C, 40 °C, 50 °C, and 60 °C), as well as cellulase enzyme concentration of 3% and 5%. The results showed that the optimal conditions for CUAEE were achieved at a temperature of 60 °C with an enzyme-solid ratio of 5%, producing a total phenolic content (TPC) of 12,097 mg EAG/g dry leaf powder and a total flavonoid content (TFC) of 2,291 EK/g dry leaf powder. The data obtained indicate that the continuous ultrasound-assisted enzymatic extraction method has the potential for large-scale production of phenolic acids and flavonoids.